Bile Acid Changes Associated With Liver Fibrosis and Steatosis in the Mexican‐American Population of South Texas - Kwan, Suet Ying (Hepatol Commun, 2020)
Biomarkers to predict risk of liver fibrosis in subjects with nonalcoholic fatty liver disease, a common risk factor for hepatocellular carcinoma, would allow for early preventive interventions. We sought to characterize bile acid profiles associated with liver fibrosis in subjects from the community‐based Cameron County Hispanic Cohort, a population in South Texas with high rates of nonalcoholic fatty liver disease, liver fibrosis and hepatocellular carcinoma. Plasma bile acid levels were measured in 390 subjects. These subjects were screened with liver elastography, detecting significant liver fibrosis in 58 subjects and steatosis in 186 subjects. Unsupervised clustering of the bile acid profiles revealed five clusters that differed by liver fibrosis, liver steatosis, liver injury, age and gender, identifying these parameters as major determinants of circulating bile acid changes. Total bile acid levels were significantly higher in subjects with fibrosis, with chenodeoxycholic acid displaying the greatest increase among individual bile acids. The primary conjugated bile acids, glycocholic and glycochenodeoxycholic acids, displayed the strongest association with fibrosis by logistic regression. High lithocholic acid levels were strongly associated with advanced fibrosis. In contrast, deoxycholic acid and total unconjugated secondary bile acids were positively associated with steatosis, whereas relative glycoursodeoxycholic acid abundance was negatively associated. Milk and yogurt intake notably contributed to fibrosis‐associated bile acid changes. In addition, multiple families within the Firmicutes phylum, Prevotellaceae, and Bacteroides species in stool significantly correlated with fibrosis‐associated and steatosis‐associated bile acid parameters, suggesting that the gut microbiome contributes to bile acid changes in the context of liver disease. Conclusion: Circulating bile acid levels were markedly but differently changed in liver fibrosis and steatosis in a high‐risk Mexican‐American population.